Psychological self-care strategies for ICU nurses under situation of public health emergency (浅谈突发公共卫生事件应急状态下重症护士的自我心理调节) - QIAN Yongcui (钱永翠) (中西医结合护理)
This paper, taking COVID-19 epidemic as an example, briefly analyzed the mental status of ICU nurses under the situation of public health emergency. Corresponding psychological self-care strategies were provided, which may help nurses enhance the awareness on psychological health problem, help them identify and address their own psychological problem. (本文以新型冠状病毒肺炎疫情为例, 简要分析重症护士在突发公共卫生事件应急状态下的心理状况, 并根据其产生原因提出相应护理对策, 使重症护士在面临突发重大公共卫生事件时重视自身的心理健康问题, 学会初步辨识自身的心理问题, 并根据自我心理状况进行自我调节。)